A comparative study on the interfacial characteristics and tensile behaviors of natural rubber composites reinforced by carbon and boron nitride nanotubes. Issue 9 (13th August 2022) - Cui, Jianzheng; Zeng, Fanlin; Yuan, Bin
Abstract: The reinforcing effect of carbon nanotubes (CNTs) and boron nitride nanotubes (BNNTs) on the interfacial characteristics and tensile behaviors of natural rubber (NR) composites were comparatively investigated using molecular dynamics simulations. A pull‐out simulation was performed to study the interfacial characteristics between CNTs, BNNTs and NR matrices. The results showed that increases of about 56.63% and 90.14% in the interfacial frictional force and interfacial shear strength were obtained for the composites by the incorporation of BNNTs than those by the incorporation of CNTs. A uniaxial tensile process was fulfilled by using the constant true strain rate method to study the mechanical properties of the NR composites reinforced by CNTs and BNNTs. The results indicated that significant increases of 22.34% and 26.59% in the Young's modulus, 4.34% and 19.28% in the yield stress, and 11.07% and 8.01% in the tensile strength were respectively achieved by the incorporation of CNTs and BNNTs as reinforcements. To deeply reveal the deformation mechanisms of the NR composites, the mean square displacement and root‐mean‐square radius of gyration of the NR chains, the fractional free volume in the NR composites, and the interfacial interaction energy were calculated and discussed accordingly. Abstract : This work comparatively investigates the reinforcing effects of carbon and boron nitride nanotubes on the interfacial characteristics and tensile behaviors of polymer composites using molecular dynamics simulations, which is valuable for the product design of high‐performance polymer composites for a wide variety of engineering applications.